Variationen eines Systemalptraums: Postmigrantische Befindlichkeiten in Burhan Qurbanis "Berlin Alexanderplatz" und Visar Morinas "Exil" - Morrien, Rita (Grenz(über)fälle und Grenzgänge: Literatur, Kunst und gesellschaftliche Dynamiken ab 2000)
Sowohl in Burhan Qurbanis "Berlin Alexanderplatz" als auch in Visar Morinas "Exil" werden Paradoxien der postmigrantischen Gesellschaft mittels einer filmischen Ästhetik des Traums reflektiert. In Qurbanis radikaler Aktualisierung von Döblins Berlin "Alexanderplatz" ist die Hauptfigur ein Schwarzer Geflüchteter, der in Deutschland auf einen Neuanfang als ‚anständiger Mensch‘ hofft. Morinas Exil erzählt die Geschichte eines scheinbar vorbildlich integrierten Migranten, der sich plötzlich als Opfer von Rassismus erlebt. Die Filme werden hier als Variationen eines Systemalbtraums gelesen, weil in beiden Fällen die kollektiven Ängste der Dominanzgesellschaft vor dem ‚parasitären Anderen‘ und die Idee der pluralen Demokratie zur Kollision gebracht werden.
Keywords: Postmigrantischer Film; Traumästhetik; Burhan Qurbani; Berlin Alexanderplatz; filmische Adaption; Visar Morina

Impulse zur Stochastik in der Oberstufe - Biehler, Rolf; Binder, Karin; Haverkamp, Michael; Kempen, Leander (Mathematikabitur „Status Quo–Quo Vadis “: Tagungsband zur Fachtagung zum Mathematikabitur am 11./12. Februar 2025 in Dresden)

Organisationen, Konventionen und Kritik. Der französische Neopragmatismus in der Organisationsforschung - Knoll, Lisa (Handbuch Organisationssoziologie)

"Future Fresko" - Charlotte Kraffts Münsterland-Blog MOMUMENT als dystopische Heimatliteratur - Morrien, Rita (Literatur in Westfalen. Beiträge zur Forschung 22)

‘School is no longer a lone wolf effort’: leadership strategies for inclusive, community-based school cultures - Woodcock, Stuart; Avramidis, Elias; Sharma, Umesh; Subban, Pearl; Sahli Lozano, Caroline; Kullmann, Harry; Loreman, Tim; Wüthrich, Sergej; Knickenberg, Margarita (School Leadership & Management)
Based on the premise that the successful implementation of inclusion is largely dependent on the educators’ commitment to inclusive ideals, this study sought to examine the ways principals promote an inclusive vision and foster the development of associated practices in their school community. The study employed an exploratory qualitative research design, collecting data through semi-structured interviews and focus groups with 12 principals of highly-ranked inclusive schools from four countries: Australia, Italy, Switzerland, and Spain. In so doing, the emphasis was placed on the principals’ perspectives and practices that contribute to the development of an inclusive school culture. The iterative process of thematic analysis revealed five broad key factors that affect and impact school inclusivity, namely: institutional commitment to a collective inclusive culture; family partnership and co-responsibility; collaboration among key stakeholders (e.g. students, teachers, other staff); students’ voice and agency; and building and sustaining inter-institutional partnerships. This paper concludes by advocating a community-based approach model to school inclusion by identifying key factors on which principals can rely to navigate material, social, and political challenges.
Keywords: Inklusive Bildung; Schulentwicklung; Schulleitung; Gemeinschaftlichkeit; Haltung

Interkulturelle Pädagogik: Fallstricke, Potenziale und Forschungsgegenstände - Pöllmann, Andreas
Das Fachbuch ermutigt dazu, eingefahrene Denkweisen zu hinterfragen und neue pädagogische Handlungsspielräume zu erschließen. Es verbindet theoretische Kontroversen mit praxisnahen Fragestellungen und eröffnet so einen Zugang zu aktuellen Debatten in Bildung und Gesellschaft. Die innovativen Konzepte der kulturellen Pluriformität und der intersektionalen Interkulturalität ermöglichen differenzierte Denk- und Handlungsperspektiven jenseits vereinfachender Kulturbegriffe. Weitere Alleinstellungsmerkmale des Buches sind die reflektierte Auseinandersetzung mit einschlägigen Fallstricken, Potenzialen und Forschungsgegenständen sowie die konsequente Einbeziehung englischsprachiger und spanischsprachiger Fachliteratur. Das komplexe Feld wird nicht vereinfacht, sondern in seiner Widersprüchlichkeit und Vielschichtigkeit ernst genommen. Dabei lädt das Buch dazu ein, pädagogische Routinen kritisch zu reflektieren, vermeintliche Selbstverständlichkeiten zu irritieren und solidarisches Handeln zu fördern. Es bietet Impulse für eine emanzipatorische interkulturelle Pädagogik, die zu Multiperspektivität, Gerechtigkeit und solidarischem Zusammenleben beiträgt.

BBNE funktioniert nicht allein - Hartwich, Katharina (Berufsbildung)

Wer plündert, wird erschossen - de Gruisbourne, Birte (Deutsche Zeitschrift für Philosophie)

Perspektiven solidarischer Erhaltungslust - de Gruisbourne, Birte (Zeitschrift für Medienwissenschaft)

Students’ mathematical feedback processes using a digital curriculum resource: A qualitative perspective - Rezat, Sebastian (ZDM – Mathematics Education)
This qualitative case study investigates how automated feedback from a widely accessible digital curriculum resource influences students’ mathematics learning. Drawing on a dialogic feedback framework, the study analyzes students’ feedback processes in an ecologically valid learning context. Grounded in a sociocultural perspective, the framework integrates Carless’ dialogic conceptualization of feedback, Shute’s feedback typology, and Vergnaud’s scheme theory. Eight eighth-graders from a German secondary school worked individually on percentage problems at home, video-recorded via online conferencing. Data included screen recordings and think-aloud protocols, which were analyzed using qualitative text analysis. Results reveal large individual differences in feedback processes—students vary in when and how they access feedback messages and how they make sense of them. Successfully solving a task after feedback does not always indicate understanding; in some cases, feedback aided procedural completion without conceptual insight. The effectiveness depended on the alignment between task design, feedback message content, and students’ actual difficulties. The study concludes that qualitative analysis of feedback processes with digital technologies in ecologically valid settings is necessary to target specific student difficulties and promote learning.

Performance evaluation of large language models in extracting requirements sets from technical documents - Gräßler, Iris; Pfeifer, Jan Niklas (1st International Symposium: March 24 – 26, 2026, Heinz Nixdorf Institute, Paderborn University)
Manufacturers operate under dynamic regulatory conditions, leading to frequently changing requirements that must be managed with high effort. AI-based requirements extraction using Large Language Models (LLMs) has the potential to support engineers in this task by analyzing large documents, for example. Existing evaluation approaches in AI-supported requirements engineering mainly assess individual requirements and their consistency with source documents, while quality criteria of requirements sets are largely neglected. This paper presents a five-step approach to evaluate the performance of current LLMs in generating requirements sets: a systematic literature review to identify quality criteria of requirements sets (1), exemplary generation of requirements sets from the Machinery Directive 2006/42/EC using LLMs (2), examination (3), evaluation (4) and comparison (5) of the generated requirements sets. The results support engineers in selecting LLMs for creating requirement sets and in evaluating future LLMs.
Keywords: Requirements Engineering; Artificial Intelligence; Large Language Models; Generative AI

(Neo-)Kantian Foundation of Foundations: The Göttingen Case - Peckhaus, Volker (New Perspectives on Neo-Kantianism and the Sciences)

1. Heiner-Müller-Jahrbuch 1: Heiner Müllers Natur.

Wave Front Sets of Nilpotent Lie Group Representations - Weich, Tobias; Budde, Julia (Journal of Functional Analysis)

Travelling Stonemasons and the Architectural Cultural Exchange between Spain, Mexico, and Peru in the 16th Century: Connections and Paths of the Toribio de Alcaraz Family - Silvestri, Marco (Art, Travel, and Exchange between Iberia and Global Geographies, c. 1400–1550)

Facetten der Germanistischen Linguistik: Bestandsaufnahme und Perspektiven - Schuster, Britt-Marie; Bubenhofer, Noah (Germanistische Linguistik. Genese, Zustand und Zukunft eines Faches im Spiegel der RGL)

Germanistische Linguistik. Genese, Zustand und Zukunft eines Faches im Spiegel der RGL

Water in the Micropores of CPO-27 Metal-Organic Frameworks: A Comprehensive Study - Kloß, Marvin; Weinberger, Christian; Tiemann, Michael (Microporous and Mesoporous Materials)
The metal-organic framework CPO-27 exhibits free coordination sites (open metal sites) and can be prepared with a wide range of metals that influence its properties. It is therefore an intriguing structure to study sorption phenomena. We analyze the water resistance and sorption behavior of these frameworks, with particular attention to the sorption mechanism in detail and the structure of the confined water molecules. For this purpose, we use manometric water vapor sorption analysis and FTIR spectroscopy. The respective metal center orchestrates both the adsorption behavior and the arrangement of the water molecules in the micropores of the framework. The extent to which water molecules form hydrogen bonds (with each other and with framework oxygen atoms) plays a crucial role in the stability of the framework towards water. Water adsorption is governed by the coordination of water molecules to the open metal sites (except for CPO-27-Cu) and subsequent H-bonding. A stepwise adsorption of water is observed, with significant differences depending on the choice of metal.

Absence of dead-core formations in chemotaxis systems with degenerate diffusion - Black, Tobias (Applied Mathematics Letters)

Symposium—Towards innovative practices in mathematics education: Teachers’ and students’ choice and use of digital resources - Pepin, Birgit; Rezat, Sebastian (Recent Advances in Mathematics Textbook Research and Development)
Abstract In this symposium we investigate students’ agency of selecting and using (digital) resources for developing their own learning paths. For that, we first review the literature related to students’ selection and use of resources in mathematics education in different pedagogical settings (presentation 1). Second, we develop insights from the different studies that participate in this symposium (presentation 2–6), at school as well as at university level. Results show that attempts have been made to provide students opportunities to develop agency of their mathematics learning, in particular with the development and provision of numerous digital tools and learning resources at university level and related to innovative pedagogical approaches. At the same time, it is not obvious how these tools and resources help students to develop deeper conceptual understandings. Certainly, students often ‘demand’ more student-centered and autonomous education approaches (e.g., at university level), also in mathematics education. Further, it seems that authentic problem-based education approaches are more motivating for students. These ‘innovative’ approaches necessitate particular types of structure and support for students. Moreover, they require different ways of providing resources that students can and want to interact with, and that help students to navigate through the curriculum to develop their own learning paths. At the same time, teachers also need support on how to orchestrate student learning with the available resources in such environments, so to be able to attend to students’ individual needs. The symposium comprised altogether six presentations: Birgit Pepin & Sebastian Rezat: Students’ agency of selecting and using (digital) resources for developing their own learning paths: An overview Annalisa Cusi & Agnese I. Telloni: Learning through digital curriculum resource design: students’ reflections on their role as designers Vilma Mesa, Lelia Burley-Sanford, Xinyi Hao, & Carlos Quiroz: Interactive features in university textbooks and their use by teachers and students Sebastian Rezat: Fostering university students’ reading and understanding of mathematical text in a flipped classroom approach with a digital marking tool Birgit Pepin & Ulises Salinas: Challenge/problem-based mathematics learning at university level: The case of the modeling week Farzad Radmehr: Problem-posing: An inclusive activity for improving teaching and learning of mathematics at university level